Dustproof styryl composition as well as preparation method and application thereof
By using compounding technology and carbon fiber reinforcement in dust-proof styrene-based compositions, the problem of poor dynamic dust protection in the prior art is solved, and better dust protection and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411572121.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, the dynamic dust-proofing effect of the dust-proof styrene-based composition is poor, resulting in the accumulation of dust after long-term operation of the air conditioner fan blades, which affects the air supply efficiency and bacterial growth.
By combining the styrene-acrylonitrile copolymers with different weight average molecular weights, the acrylonitrile content is adjusted to be no less than 26 wt%, and an appropriate amount of carbon fiber is added to synergistically distribute it to improve the dynamic dust-proof effect of the composition.
It significantly improves the dynamic dustproof effect of air conditioning fan blade materials, improves the surface resistivity and mechanical properties, makes the surface of fan blade materials smoother and reduces dust accumulation.
Smart Images

Figure BDA0005120750300000011 
Figure BDA0005120750300000041 
Figure BDA0005120750300000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material modification, and more specifically, relates to a dustproof styrene-based composition and a preparation method and application thereof. Background Art
[0002] Styrene-acrylonitrile copolymer (styrene-based) is a thermoplastic polymer material with high strength, excellent transparency, and easy processing and molding. It is widely used in home appliances, office supplies, daily necessities and other fields.
[0003] Adding glass fiber to the styrene base can significantly improve the strength and rigidity of the material and reduce the linear thermal expansion coefficient. It has excellent dimensional stability and is therefore suitable for parts with higher requirements for strength and dimensional stability, such as air conditioning fan blades. However, during use, the glass fiber may be exposed on the surface of the resin matrix, resulting in a rough surface of the fan blade material. Dust is easily accumulated during long-term operation, resulting in a decrease in air supply efficiency and easy breeding of bacteria.
[0004] In the prior art, the surface resistivity of the material can be increased by replacing part of the glass fiber with carbon fiber, which can improve static dust prevention to a certain extent. However, the effect on dynamic dust prevention is limited. For air-conditioning fan blades that are in long-term operation, a large amount of dust will still accumulate on the surface of the fan blades after running for a period of time. Summary of the invention
[0005] The object of the present invention is to overcome the defects or shortcomings of the prior art dust-proof styrene-based composition, that is, the dynamic dust-proof effect is poor, and to provide a dust-proof styrene-based composition.
[0006] Another object of the present invention is to provide a method for preparing the dustproof styrene-based composition.
[0007] Another object of the present invention is to provide application of the dustproof styrene-based composition.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions:
[0009] A dustproof styrene-based composition comprises the following components calculated in parts by weight:
[0010]
[0011] Wherein, the weight average molecular weight of the styrene-acrylonitrile copolymer A is 100,000 to 120,000, and the acrylonitrile content is not less than 26 wt %;
[0012] The weight average molecular weight of the styrene-acrylonitrile copolymer B is 500,000 to 600,000, and the acrylonitrile content is not less than 26 wt %;
[0013] The reinforcing agent contains carbon fibers, wherein the content of the carbon fibers is not less than 50 wt %.
[0014] In the present invention, by using styrene-acrylonitrile copolymers with different weight-average molecular weights for compounding, adjusting the acrylonitrile content therein to not less than 26wt%, and coordinating with a certain amount of carbon fiber, the dynamic dustproof effect of the composition can be effectively improved. Specifically: low molecular weight styrene-acrylonitrile copolymers have excellent processing performance, but their viscosity is relatively low. During the injection molding process of fan blades, the orientation and distribution of the reinforcing agent are relatively random, and it is easy to be exposed, thereby greatly reducing the dynamic dustproof effect of the fan blades; by compounding a certain amount of high molecular weight styrene-acrylonitrile copolymers, the orientation of the reinforcing agent can be limited, so that it is better distributed in the system, thereby greatly reducing the exposure, and making the fan blade material have a smoother surface; further adding carbon fiber with excellent conductive properties, the surface resistivity of the fan blade material is greatly reduced, and the mechanical properties of the fan blade material are also significantly improved; the three cooperate with each other, thereby greatly improving the dynamic dustproof effect of the fan blade prepared using the material.
[0015] It should be noted that, in the dustproof styrene-based composition of the present invention, the content of the styrene-acrylonitrile copolymer A is preferably not less than 30 wt %.
[0016] It should be noted that the weight average molecular weight of the styrene-acrylonitrile copolymer described in the present invention is measured by gel permeation chromatography (GPC) using a TDA 302 GPC analyzer produced by Viscotek, USA, with polystyrene as the standard sample, tetrahydrofuran as the eluent, a flow rate of 1.0 mL / min, and a test temperature of 30°C.
[0017] In the present invention, the weight average molecular weight of the styrene-acrylonitrile copolymer A is 100000-120000, for example but not limited to 100000, 101000, 102000, 103000, 104000, 105000, 106000, 107000, 108000, 109000, 110000, 111000, 112000, 113000, 114000, 115000, 116000, 117000, 118000, 119000 or 120000, etc. can all realize the present invention. Further, the weight average molecular weight of the styrene-acrylonitrile copolymer A is 105000-115000.
[0018] The acrylonitrile content in the styrene-acrylonitrile copolymer A is not less than 26wt%, for example but not limited to not less than 26wt%, 26.5wt%, 27wt%, 27.5wt%, 28wt%, 28.5wt%, 29wt%, 29.5wt%, 30wt%, 30.5wt%, 31wt%, 31.5wt%, 32wt%, 32.5wt%, 33wt%, 33.5wt%, 34wt%, 34.5wt% or 35wt%, etc. can all realize the present invention. Further, the acrylonitrile content in the styrene-acrylonitrile copolymer A is 27-33wt%.
[0019] The weight average molecular weight of the styrene-acrylonitrile copolymer B is 500000-600000, for example, but not limited to 500000, 505000, 510000, 515000, 520000, 525000, 530000, 535000, 540000, 545000, 550000, 555000, 560000, 565000, 570000, 575000, 580000, 585000, 590000, 595000 or 600000, etc. can all realize the present invention. Further, the weight average molecular weight of the styrene-acrylonitrile copolymer B is 520000-570000. The acrylonitrile content in the styrene-acrylonitrile copolymer B is not less than 26wt%, for example but not limited to not less than 26wt%, 26.5wt%, 27wt%, 27.5wt%, 28wt%, 28.5wt%, 29wt%, 29.5wt%, 30wt%, 30.5wt%, 31wt%, 31.5wt%, 32wt%, 32.5wt%, 33wt%, 33.5wt%, 34wt%, 34.5wt% or 35wt%, etc. can all realize the present invention. Further, the acrylonitrile content in the styrene-acrylonitrile copolymer B is 27-33wt%.
[0020] Specifically, the acrylonitrile content is characterized by infrared spectroscopy combined with nuclear magnetic hydrogen spectrum and nuclear magnetic carbon spectrum.
[0021] The content of carbon fiber in the reinforcing agent in the present invention is not less than 50wt%, for example but not limited to not less than 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%, etc. can realize the present invention.
[0022] Furthermore, the content of carbon fiber in the reinforcing agent is 50wt% to 70wt%.
[0023] Furthermore, the reinforcing agent may include one or more of glass fiber, talcum powder, wollastonite, whisker or glass microbeads. The corresponding reinforcing agent may be selected according to the mechanical properties required for the actual application, and the dynamic dustproof effect may be achieved.
[0024] Furthermore, the reinforcing agent is a mixture of glass fiber and carbon fiber.
[0025] Specifically, the average diameter of the glass fiber is 6-20 μm.
[0026] The average diameter of the carbon fibers is 13-18 μm.
[0027] Specifically, the average diameter is tested with reference to GB / T 7690.5-2013 Method A standard.
[0028] It should be noted that the styrene-acrylonitrile copolymer in the present invention can be commercially available or homemade.
[0029] Specifically, the preparation method of the styrene-acrylonitrile copolymer includes but is not limited to the following preparation method:
[0030] Obtained by polymerization of acrylonitrile monomer and styrene monomer.
[0031] Specifically, the polymerization temperature is 150 to 160° C., and the polymerization time is 1 to 4 hours.
[0032] Specifically, in order to control the weight average molecular weight of the styrene-acrylonitrile copolymer, a molecular weight regulator is added during a suitable polymerization time to terminate the reaction to obtain styrene-acrylonitrile copolymers with different molecular weights.
[0033] Specifically, the amount of the molecular weight regulator added is 0.1-0.2 wt % of the total amount of the monomers.
[0034] Specifically, the acrylonitrile content in the styrene-acrylonitrile copolymer is controlled by the feeding ratio of the styrene monomer and the acrylonitrile monomer; the mass ratio of the acrylonitrile monomer to the styrene monomer is 26:74 to 35:65.
[0035] Furthermore, the dustproof styrene-based composition also includes 1.5 to 5 parts of a lubricant, and the lubricant is an amide lubricant.
[0036] Specifically, the amide lubricant includes one or more of erucamide, oleamide or N,N'-ethylenebisstearamide.
[0037] Furthermore, the dustproof styrene-based composition comprises the following components calculated in parts by weight:
[0038]
[0039] Furthermore, the compatibilizer includes maleic anhydride polymer and / or acrylate polymer.
[0040] Specifically, the maleic anhydride polymer may be one or more of ABS-g-MAH, AS-g-MAH or styrene-maleic anhydride copolymer.
[0041] Specifically, the acrylic polymer may be one or more of ABS-g-GMA, methyl methacrylate, and styrene-acrylonitrile-glycidyl methacrylate copolymer.
[0042] Furthermore, the dustproof styrene-based composition also includes 0.1 to 5 parts of an auxiliary agent.
[0043] Specifically, the auxiliary agent includes one or more of an antioxidant, a weathering agent or a toner.
[0044] In the present invention, commonly used antioxidants can be selected according to the prior art, such as but not limited to hindered phenol antioxidants and / or phosphite antioxidants.
[0045] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (Irganox 1098), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 259), β-(4-hydroxy-3,5-di-tert-butylphenyl)propionic acid n-octadecyl (Irganox 1076) or 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylate]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane (ADK AO-80).
[0046] The phosphite antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite (Irganox 168), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36) or 627A.
[0047] The present invention also protects a method for preparing the above-mentioned dustproof styrene-based composition, comprising the following steps:
[0048] S1. The dustproof styrene-based composition above except the reinforcing agent is mixed to obtain a premix;
[0049] S2. The premix is fed through the main feeding port, and the reinforcing agent is fed through the side feeding port, and the mixture is melt-blended and extruded to obtain granules.
[0050] Specifically, a high-speed mixer is used for mixing in step S1.
[0051] Specifically, the mixing temperature is 20 to 50° C., the mixing speed is 100 to 800 rpm, and the mixing time is 2 to 5 minutes.
[0052] Furthermore, the extrusion granulation adopts a twin-screw extruder.
[0053] Specifically, the feeding speed of the twin-screw extruder is 200-350 rpm, the main engine speed is 100-500 rpm, and the vacuum degree is ≤0.1 MPa.
[0054] Specifically, the temperature of zone 1 of the twin-screw extruder is 220-250°C, the temperature of zone 2 is 220-240°C, the temperature of zone 3 is 210-220°C, the temperature of zone 4 is 210-230°C, the temperature of zone 5 is 210-230°C, and the die temperature is 220-230°C.
[0055] Specifically, the aspect ratio of the twin-screw extruder is (36-48):1.
[0056] The present invention also protects the use of the dustproof styrene-based composition in the preparation of household appliance materials, and is particularly suitable for air conditioner fan blade materials.
[0057] The present invention also provides an air-conditioning fan blade, which is prepared by using the dust-proof styrene-based composition.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] The present invention provides a dustproof styrene-based composition. The dynamic dustproof effect of the composition can be effectively improved by compounding a styrene-acrylonitrile copolymer with a specific weight-average molecular weight, adjusting its acrylonitrile content, and adding an appropriate amount of carbon fiber. The composition is particularly suitable for application in materials such as air conditioner fan blades. DETAILED DESCRIPTION
[0060] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0061] 1. Raw materials used in each embodiment and comparative example:
[0062] Styrene-acrylonitrile copolymer A:
[0063] Styrene-acrylonitrile copolymer A1: acrylonitrile content 33wt%, weight average molecular weight 110000, homemade;
[0064] Styrene-acrylonitrile copolymer A2: acrylonitrile content 33wt%, weight average molecular weight 118000, homemade;
[0065] Styrene-acrylonitrile copolymer A3: acrylonitrile content 33wt%, weight average molecular weight 102000, homemade;
[0066] Styrene-acrylonitrile copolymer A4: SAN-355, acrylonitrile content of 31.8wt%, weight average molecular weight of 113000; purchased from Daqing Petrochemical;
[0067] Styrene-acrylonitrile copolymer A5: acrylonitrile content 27wt%, weight average molecular weight 110000, homemade;
[0068] Styrene-acrylonitrile copolymer A6: acrylonitrile content 33wt%, weight average molecular weight 80000, homemade;
[0069] Styrene-acrylonitrile copolymer A7: acrylonitrile content 33wt%, weight average molecular weight 150000, homemade;
[0070] Styrene-acrylonitrile copolymer A8: acrylonitrile content 25wt%, weight average molecular weight 110000, homemade;
[0071] Styrene-acrylonitrile copolymer B:
[0072] Styrene-acrylonitrile copolymer B1: acrylonitrile content 33wt%, weight average molecular weight 530000, homemade;
[0073] Styrene-acrylonitrile copolymer B2: acrylonitrile content 33wt%, weight average molecular weight 510000, homemade;
[0074] Styrene-acrylonitrile copolymer B3: acrylonitrile content 33wt%, weight average molecular weight 560000, homemade;
[0075] Styrene-acrylonitrile copolymer B4: acrylonitrile content 33wt%, weight average molecular weight 590000, homemade;
[0076] Styrene-acrylonitrile copolymer B5: EPA-100, acrylonitrile content of 32 wt%, weight average molecular weight of 520,000; purchased from Weihai Jinhesi Chemical;
[0077] Styrene-acrylonitrile copolymer B6: acrylonitrile content 28wt%, weight average molecular weight 530000, homemade;
[0078] Styrene-acrylonitrile copolymer B7: acrylonitrile content 33wt%, weight average molecular weight 450000, homemade;
[0079] Styrene-acrylonitrile copolymer B8: acrylonitrile content 33wt%, weight average molecular weight 650000, homemade;
[0080] Styrene-acrylonitrile copolymer B9: acrylonitrile content 25wt%, weight average molecular weight 530000, homemade;
[0081] The homemade styrene-acrylonitrile copolymer described in the present invention is prepared by the following preparation method:
[0082] The method comprises polymerizing acrylonitrile monomer and styrene monomer at 150-160° C. for 1-4 hours, and adding a molecular weight regulator (the amount of which is 0.15 wt% of the total amount of monomers) to terminate the reaction at the end of the polymerization to obtain a styrene-acrylonitrile copolymer with a weight average molecular weight. The weight average molecular weight can be controlled by adjusting the time of adding the molecular weight regulator, and the acrylonitrile content in the styrene-acrylonitrile copolymer can be controlled by adjusting the feeding ratio of the styrene monomer and the acrylonitrile monomer.
[0083] Styrene-acrylonitrile copolymer C: KFA-180, acrylonitrile content of 32 wt%, weight average molecular weight of 180,000, purchased from Liaoning Jinfa;
[0084] Enhancer:
[0085] Reinforcement 1: Glass fiber: ECS13-4.5-534, average diameter 13 μm, purchased from Jushi, China;
[0086] Reinforcement 2: Carbon fiber: PX35CA0250-65, average diameter 14 μm, purchased from Toray, Japan;
[0087] Enhancer 3: Talc: TYT-777A, purchased from Haicheng Tianyuan Chemical;
[0088] Compatibilizer:
[0089] Compatibilizer 1: maleic anhydride polymer, styrene-maleic anhydride copolymer, SMA700, purchased from Jiaxing Huawen;
[0090] Compatibilizer 2: acrylic polymer, styrene-acrylonitrile-glycidyl methacrylate copolymer, SAG-002, purchased from Jiayirong;
[0091] Lubricant:
[0092] Lubricant 1: erucamide, commercially available;
[0093] Lubricant 2: oleamide, commercially available;
[0094] Lubricant 3: N,N'-ethylene bisstearamide, commercially available;
[0095] Lubricant 4: zinc stearate, commercially available;
[0096] Additives:
[0097] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2; it should be noted that the same raw materials are used in the parallel experiments of the embodiments and comparative examples of the present invention.
[0098] 2. The styrene-based compositions described in the embodiments and comparative examples of the present invention are prepared according to the formulations in Tables 1 to 2 by the following method, comprising the following steps:
[0099] S1. The other components except the reinforcing agent were premixed in a high mixer according to the proportion, the mixing temperature was 30 ° C, the mixing speed was 500 rpm, the mixing time was 3 minutes, and the premix was uniformly mixed;
[0100] S2. The premix of step S1 is fed into a twin-screw extruder through the main feed port, and the reinforcing agent is fed through the side feed port, and the mixture is melt-blended and extruded to obtain granules; the feeding speed of the twin-screw extruder is 275 rpm, the main engine speed is 350 rpm, and the vacuum degree is 0.08 MPa.
[0101] Specifically, the temperature of zone 1 of the twin-screw extruder is 235°C, the temperature of zone 2 is 230°C, the temperature of zone 3 is 215°C, the temperature of zone 4 is 220°C, the temperature of zone 5 is 220°C, and the die temperature is 225°C.
[0102] Specifically, the length-to-diameter ratio of the twin-screw extruder is 48:1.
[0103] 3. Performance Testing
[0104] (1) Surface resistivity measurement: The styrene-based compositions prepared in each example and comparative example were injection molded into a 3 mm*10 mm*10 mm square plate specimen, and the surface resistivity was measured according to ASTM D257-2014;
[0105] (2) Determination of dynamic dustproof grade: First, prepare the crossflow fan blade. The preparation of the crossflow fan blade is to use an injection molding machine to inject the end cover, top cover, fan blade and other related parts of the crossflow fan blade. Then, the most commonly used ultrasonic welding technology in the industry is used to weld the crossflow fan blade suitable for use in the indoor unit of the air conditioner. The mass of the crossflow fan blade is 500g. After continuous operation at a speed of 800 revolutions per minute for 1000 hours, the crossflow fan blade is weighed. The weight increase of more than 2% is rated as level 4, the weight increase of 1-2% (excluding 2%) is rated as level 3, the weight increase of 0.5-1% (excluding 1%) is rated as level 2, and the weight increase of less than 0.5% (excluding 0.5%) is rated as level 1.
[0106] (3) Tensile strength measurement: The styrene-based composition in each example and comparative example was injection molded into an ISO standard dumbbell-shaped tensile specimen and tested with reference to ISO 527-1-2012 standard.
[0107] Examples 1 to 18 and Comparative Examples 1 to 8
[0108] The dosage of each component and the performance test results of the compositions in the examples and comparative examples are shown in Tables 1-2.
[0109] Table 1 Amount (unit: weight parts) and properties of each component in the dustproof styrene-based composition in Examples 1 to 14
[0110]
[0111]
[0112] Table 2 Amount (unit: weight parts) and properties of each component in the styrene-based composition in Examples 15 to 18 and Comparative Examples 1 to 8
[0113]
[0114]
[0115] It can be seen from Table 1 that the dust-proof styrene-based compositions prepared in various embodiments of the present invention have good dynamic dust-proof effects. Specifically, the dynamic dust-proof grade is not lower than level 2, and the surface resistivity is not higher than 3.6*10 5 Ω.
[0116] It can be seen from Examples 1 to 3 that when the weight average molecular weight of the styrene-acrylonitrile copolymer A is further adjusted to 105,000 to 115,000, the comprehensive performance of the dustproof styrene-based composition obtained is better.
[0117] It can be seen from Examples 1 and 4 to 6 that when the weight average molecular weight of the styrene-acrylonitrile copolymer B is 520,000 to 570,000, the comprehensive performance of the dustproof styrene-based composition obtained is better.
[0118] It can be seen from Comparative Examples 1 to 4 that when the weight average molecular weight of styrene-acrylonitrile copolymer A or B is too small or too large, it will affect the dispersion and distribution of glass fiber and carbon fiber in the system, resulting in a lower dynamic dustproof grade of the material.
[0119] It can be seen from Comparative Example 5 that if only a styrene-acrylonitrile copolymer with a moderate weight average molecular weight is used, the dustproof grade of the prepared composition is still poor.
[0120] It can be seen from Comparative Examples 6 and 7 that when the acrylonitrile content in the styrene-acrylonitrile copolymer A or B used is low, the dust resistance level of the obtained styrene-based composition is poor.
[0121] It can be seen from Comparative Example 8 that if the carbon fiber accounts for less than 50 wt % in the reinforcing agent, the dustproof grade of the obtained dustproof styrene-based composition is worse than that of the embodiment.
[0122] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A dust-proof styrene-based composition, characterized in that The composition comprises the following components calculated by weight: Wherein, the weight average molecular weight of the styrene-acrylonitrile copolymer A is 100,000 to 120,000, and the acrylonitrile content is not less than 26 wt %; The weight average molecular weight of the styrene-acrylonitrile copolymer B is 500,000 to 600,000, and the acrylonitrile content is not less than 26 wt %; The reinforcing agent contains carbon fibers, wherein the content of the carbon fibers is not less than 50 wt %.
2. The dust-proof styrene-based composition according to claim 1, characterized in that: The weight average molecular weight of the styrene-acrylonitrile copolymer A is 105,000-115,000.
3. The dust-proof styrene-based composition according to claim 1, characterized in that: The weight average molecular weight of the styrene-acrylonitrile copolymer B is 520,000-570,000.
4. The dust-proof styrene-based composition according to claim 1, characterized in that: It also includes 1.5 to 5 parts of a lubricant, which is an amide lubricant; preferably, the amide lubricant includes one or more of erucamide, oleamide or N,N'-ethylene bisstearamide.
5. The dust-proof styrene-based composition according to claim 1, characterized in that: The compatibilizer includes maleic anhydride polymer and / or acrylate polymer.
6. The dust-proof styrene-based composition according to claim 1, characterized in that: The reinforcing agent also includes one or more of glass fiber, talcum powder, wollastonite, whisker or glass microbeads.
7. The dust-proof styrene-based composition according to claim 1, characterized in that: The acrylonitrile content in the styrene-acrylonitrile copolymer A is 27-33 wt %; the acrylonitrile content in the styrene-acrylonitrile copolymer B is 27-33 wt %.
8. The dust-proof styrene-based composition according to claim 1, characterized in that: It also includes 0.1 to 5 parts of auxiliary agents.
9. A method for preparing the dustproof styrene-based composition according to any one of claims 1 to 8, characterized in that: The steps include: S1. The dustproof styrene-based composition above except the reinforcing agent is mixed with the other components to obtain a premix; S2. The premix is fed through the main feeding port, and the reinforcing agent is fed through the side feeding port, and the mixture is melt-blended and extruded to obtain granules.
10. Use of the dustproof styrene-based composition according to any one of claims 1 to 8 in the preparation of household appliance materials.
Citation Information
Patent Citations
Acrylonitrile-acrylate-styrene resin composite and preparation method thereof
CN101857701A
Aromatic polycarbonate resin composition and molded article thereof
CN102333821A
Glass fiber reinforced fire retardation styrene-acrylonitrile material and preparation method thereof
CN103834115A
Preparation method of styrene-acrylonitrile copolymer
CN110982004A
Polycarbonate resin / ABS graft copolymer / SAN blends
CN1331727A